Analysis of the climate change impact on water availability and the links between water pollution and economy for sustainable water resource management in Kaski District, Nepal. Issue 8 (8th July 2022) - Chapagain, Saroj Kumar; Aryal, Anil; Mohan, Geetha; Shrestha, Sadhana; Mishra, Binaya Kumar; Fukushi, Kensuke
Abstract: The newly enacted national water policy is envisioned as ensuring water sustainability in Nepal. Despite theoretical pertinence, questions remain about the effective implementation due to limited studies on key aspects of sustainability, such as water supply and demand, pollution, and impacts of climate change and socio-economic growth. This study analyses the current and future availability of water under climate change scenarios and determines water resources carrying capacity (WRCC) as the maximum socio-economic growth that can be supported in a case study on the Kaski District, Nepal. Annual average water availability was estimated to be 11, 030.7 million cubic meters (MCM) for the baseline period (1992–2010), and 7, 677.4 and 7, 674.2 MCM for the future period (2022–2050) under the representative concentration pathway (RCP) 4.5 and 8.5 emission scenarios, respectively. For the baseline period, WRCC far exceeds the current population; therefore, water resources will not be a limiting factor for local socio-economic development. Nevertheless, sustainable water infrastructure development policies are necessary to ensure a reliable water supply able to cope with increasing seasonal variability and declining future water availability. A total of 30, 049 tons of biological oxygen demand (BOD) loads were estimated based on the economic activities of the Kaski District in 2011, with the direct and indirect sectoral roles of water pollution determined for the first time. Rather than a single pollution control strategy based on pollution loads, multiple sector-specific strategies are necessary to effectively implement water pollution control policies. HIGHLIGHTS: A decline in water availability and substantial seasonal variability is projected. Investing in water storage facilities and adequate supply systems are necessary for a reliable water supply. Sector-specific water pollution control measures should be considered. Analysis of direct and indirect sectoral pollution provides a strong basis for effective water pollution control policies. Graphical Abstract